In vivo appraisal of oxidative stress response, cell ultrastructural aberration and accumulation in Juvenile Scylla serrata exposed to uranium. (August 2022) - Barathkumar, S.; Padhi, R.K.; Parida, P.K.; Marigoudar, S.R.
Abstract: In vivo studies were performed to evaluate the organ specific tissue accumulation and cellular toxicity of uranium to mud crab Scylla serrata . The specimens were acclimated in natural seawater and the exposure to 50–250 μ g/L uranium was investigated up to 60 days. The present study examined the effects of concentration and duration of uranium exposure in the tissue of S. serrata at cellular and subcellular level using scanning electron microscopy and bright field transmission electron microscopy in addition to histological analysis. The results indicated that accumulation of U in S. serrata was organ specific and followed the order gills > hepatopancreas > muscle. The response of key antioxidant enzyme activities such as SOD, GPx and CAT in different organs of crabs indicated oxidative stress due to U in the ambient medium and tissue. At 50 and 100 μg/L of U exposure, individuals were able to acclimate the oxidative stress and withstand the uranium exposure. This acclimation could not be sustained at higher concentrations (250 μg/L), affecting the production of CAT in the tissues. Cellular and subcellular changes were observed in the hemocytes with reduction in their number in consonance with the antioxidant enzymes. Histological aberrations like lamellar disruption of gill, necrosis of hepatopancreas, disruption and rupture of muscle bundles were observed at different concentrations and were severe at higher concentration (250 μg/L). Necrosis was observed in the electron micrographs of tissues shortly after 15 days of exposure. SEM micrograph clearly shows disrupted lamellae, folding of marginal canal and reduction of inter lamellar spaces in the gills of crab exposed to high concentration of uranium. Mitochondrial anomalies are reported for the first time in the present study in addition to the subcellular changes and vacuoles on exposure uranium in the cells of gill and hepatopancreas. Graphical abstract: Image 1 Highlights: Scylla serrata was exposed to seawater containing 0, 50, 100 and 250 μg/L uranium. Uranium preferably accumulated in gills and hepatopancreas and less in muscle tissue used for human consumption. Histopathological lesions observed in gill, hepatopancreas and muscle. SEM analysis showed lamellar fusion and epithelial degradation in gill. Structural deformation of mitochondria observed.